Comparison of Pathomorphological Changes in the Brain and Other Organs in Women Who Died as a Result of Ischaemic Vertebrobasilar and Hemispheric Strokes (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article presents the results of pathomorphological studies in women who died as a result of ischaemic stroke. The obtained data confirm the concept of pathogenetic heterogeneity of ischaemic strokes and the necessity of the earliest possible pathogenetically grounded treatment.